2011
DOI: 10.1186/1744-8069-7-37
|View full text |Cite
|
Sign up to set email alerts
|

TRPV3 and TRPV4 Ion Channels are Not Major Contributors to Mouse Heat Sensation

Abstract: BackgroundThe discovery of heat-sensitive Transient Receptor Potential Vanilloid (TRPV) ion channels provided a potential molecular explanation for the perception of innocuous and noxious heat stimuli. TRPV1 has a significant role in acute heat nociception and inflammatory heat hyperalgesia. Yet, substantial innocuous and noxious heat sensitivity remains in TRPV1 knockout animals. Here we investigated the role of two related channels, TRPV3 and TRPV4, in these capacities. We studied TRPV3 knockout animals on b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
154
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(163 citation statements)
references
References 35 publications
7
154
1
1
Order By: Relevance
“…Second, we used 129S1/SvImJ mice in these studies, and this strain may be inferior to C57BL/6 mice in behavioral assays (42,43). It has been noted that there are temperature-sensing differences between mouse strains (44,45), and we cannot generalize our results to other strains or species.…”
Section: Discussionmentioning
confidence: 61%
“…Second, we used 129S1/SvImJ mice in these studies, and this strain may be inferior to C57BL/6 mice in behavioral assays (42,43). It has been noted that there are temperature-sensing differences between mouse strains (44,45), and we cannot generalize our results to other strains or species.…”
Section: Discussionmentioning
confidence: 61%
“…Recent studies, however, highlighted the limitation of using animal models in understanding human physiology (19,20). Capsaicin receptors in human sensory neurons exhibit significant heterogeneity that might reflect differences in the subunit composition (37).…”
Section: Discussionmentioning
confidence: 99%
“…rat and mouse) TRPV3 is found to express predominantly in keratinocytes (13). The difference in tissue distribution calls for caution in interpreting the applicability of behavior and knock-out studies in rodents to human physiology (19,20). Indeed, it was previously found that TRPV1 and TRPV3 subunits co-assemble into heteromeric channels (14,21).…”
mentioning
confidence: 99%
“…The remaining members of the TRPV subfamily (TRPV2-6) share 30-50% sequence similarity with TRPV1 (ref. 7); nevertheless they are vanilloid insensitive and play a minimal role in temperature sensation [8][9][10][11] , suggesting that 'minimal' TRPV1 is only partly representative of the other TRPV subfamily members.…”
mentioning
confidence: 99%